(untitled) (Brazilian Journal of Radiation Sciences, 2019)
The study of artificial radionuclides dispersion into the environment is very important to control the nuclear waste discharges, nuclear accidents and nuclear weapons testing. The accidents in Fukushima Daiichi Nuclear Power Plant and Chernobyl Nuclear Power Plant, released several radionuclides in the environment by aerial deposition and liquid discharge, with various level of radioactivity. The 90Sr was one of the elements released into the environment. The 90Sr is produced by nuclear fission with a physical half-life of 28.79 years with decay energy of 0.546 MeV. The aims of this study are to evaluate the precision and accuracy of three methodologies for the determination of 90Sr in water samples: Cerenkov, LSC direct method and with radiochemical separation. The performance of the methodologies was evaluated by using two scintillation counters (Quantulus and Hidex). The parameters Minimum Detectable Activity (MDA) and Figure Of Merit (FOM) were determined for each method, the precision and accuracy were checked using 90Sr standard solutions.